The Determinants of Individual Taxpayers’ Tax Compliance Behaviour in Peninsular Malaysia - Tan Swee Kiow; Mohd Fuad Mohd Salleh; Aza Azlina Bt Md Kassim (International Business and Accounting Research Journal, 2017)
The findings from this review suggested that tax compliance behaviour of individual taxpayers is influenced by ethical perception of individual taxpayers and their ethical perception is affected by public governance and transparency in government operations. Ethical perception plays an important role for individual taxpayers to report their income correctly. Ethical perception varies from an individual to another, which influenced by changes in their surroundings and their experiences when interact with government. Perceptions of how taxpayers’ money is being utilised, benefits they derived from government or others evade to pay tax are considered as possible factors influencing their compliance behaviour. Taxpayers will be more compliance if government use tax monies wisely or when taxpayers get benefits for the taxes paid in terms of public goods and social amenities that they prefer. Transparent surroundings will enhance taxpayers’ confidence in public bodies. Taxpayers are concerned on transparency in public procurement as lack of transparency may cause corruption and reduces public sector efficiency. In contrast, scholars argued that greater degree of transparency could lead to less trust as it will be easier for taxpayers to audit government and they might blame government for small mistakes.